2020
DOI: 10.1016/j.pocean.2020.102343
|View full text |Cite
|
Sign up to set email alerts
|

Primary production and depth drive different trophic structure and functioning of fish assemblages in French marine ecosystems

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 105 publications
2
34
0
Order By: Relevance
“…The large abundance of Clupeidae in large whiting stomachs reflects that the winter spawning migration of these species in the EEC represents an important trophic opportunity for whiting during a nutrient-poor period. Previous studies reported a particularly high energetic value for these species [ 63 , 76 ]. Energy content analyzes performed on 78 species taken from the northeast Atlantic Ocean thus revealed that C .…”
Section: Discussionmentioning
confidence: 99%
“…The large abundance of Clupeidae in large whiting stomachs reflects that the winter spawning migration of these species in the EEC represents an important trophic opportunity for whiting during a nutrient-poor period. Previous studies reported a particularly high energetic value for these species [ 63 , 76 ]. Energy content analyzes performed on 78 species taken from the northeast Atlantic Ocean thus revealed that C .…”
Section: Discussionmentioning
confidence: 99%
“…Isotopic difference between the species may support this assumption. Less negative δ 13 C value is commonly interpreted as a higher dependency on benthic-derived organic matter (Carlier et al, 2007;Cresson et al, 2020;Duffill Telsnig et al, 2019;Kopp et al, 2015;Le Loc'h et al, 2008). Isotopic ratios measured for sole can thus track the dependency of this species on the organic matter from the soft bottom sediment, potentially processed by the microbial pathway.…”
Section: Influence Of Diet and Feeding Habitat On Hg Species Concentr...mentioning
confidence: 99%
“…Compared with prior knowledge, EcoDiet revealed higher contributions of benthic and invertebrate compartments to the diet of most species, resulting in lower TLs for many predators and lower importance of the pelagic pathways in biomass flows. This suggests that the overall functioning of the Celtic Sea may be closer to that of the neighboring English Channel than that of the pelagic‐dominated Bay of Biscay (Cresson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%